2021
DOI: 10.1186/s12974-021-02082-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute systemic LPS-exposure impairs perivascular CSF distribution in mice

Abstract: Background The exchange of cerebrospinal (CSF) and interstitial fluid is believed to be vital for waste clearance in the brain. The sleep-dependent glymphatic system, which is comprised of perivascular flow of CSF and is largely dependent on arterial pulsatility and astrocytic aquaporin-4 (AQP4) expression, facilitates much of this brain clearance. During the last decade, several observations have indicated that impaired glymphatic function goes hand in hand with neurodegenerative diseases. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 41 publications
(64 reference statements)
3
24
1
Order By: Relevance
“…A recent study elucidated how the glymphatic system reacts to a peripheral inflammatory challenge [ 115 ]. In that study, there was reduced perivascular CSF flow as soon as three hours after peripheral LPS treatment at a single dose of 1 mg/kg in mice [ 115 ].…”
Section: How Does Neuroinflammation Affect the Glymphatic System?mentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study elucidated how the glymphatic system reacts to a peripheral inflammatory challenge [ 115 ]. In that study, there was reduced perivascular CSF flow as soon as three hours after peripheral LPS treatment at a single dose of 1 mg/kg in mice [ 115 ].…”
Section: How Does Neuroinflammation Affect the Glymphatic System?mentioning
confidence: 99%
“…A recent study elucidated how the glymphatic system reacts to a peripheral inflammatory challenge [ 115 ]. In that study, there was reduced perivascular CSF flow as soon as three hours after peripheral LPS treatment at a single dose of 1 mg/kg in mice [ 115 ]. Other factors known to influence the glymphatic function were measured; respiration, cortical blood flow, astrogliosis, and AQP4 polarization were surprisingly unchanged at three hours, despite the reduction in CSF flow.…”
Section: How Does Neuroinflammation Affect the Glymphatic System?mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, systemic inflammation influences the function of the glymphatic system based on the evidence that the structure and function of the glymphatic system are closely related to that of the BBB (Verheggen et al, 2018 ). Notably, a recent study found that lipopolysaccharide-induced systemic inflammation reduced perivascular CSF tracer flow and penetration into the parenchyma (Manouchehrian et al, 2021 ). These observations may be beneficial for our understanding of the role of systemic inflammation in glymphatic clearance.…”
Section: Glymphatic Function Affected By Surgerymentioning
confidence: 99%